Analysis of the associations between variables derived throughout velocity-based training device and jumping performances in youth soccer players: Multiple regression study - Bendic, V.; Gilic, B.; Lastre, D.; Peric, I.; Sekulic, D. (Acta Gymnica, 2021)
Background: It has been suggested that velocity-based training (VBT) improves real-life performance in sports, such as jumping, but studies rarely examined the associations between variables derived during VBT (VBT-variables) and jumping performances.